2004
DOI: 10.3748/wjg.v10.i9.1353
|View full text |Cite
|
Sign up to set email alerts
|

Plasma erythropoietin levels in anaemic and non-anaemic patients with chronic liver diseases

Abstract: AIM:To investigate the serum erythropoietin (Epo) levels in patients with chronic liver diseases and to compare to subjects with iron-deficiency anaemia and healthy controls. METHODS:We examined 31 anaemic (ALC) and 22 nonanaemic (NALC) cirrhotic patients, 21 non-anaemic subjects with chronic active hepatitis (CAH), 24 patients with irondeficiency anaemia (ID) and 15 healthy controls. Circulating Epo levels (ELISA; R&D Systems, Europe Ltd, Abingdon, UK) and haemoglobin (Hb) concentration were determined in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Finally, it seems that serum Epo values in cirrhotic patients are only detectable when Hb is Ͻ12 g/dL. This value is lower than that observed in anemic patients with iron deficiency and seems blunted and inadequate compared with the degree of anemia (15).…”
Section: Discussionmentioning
confidence: 95%
“…Finally, it seems that serum Epo values in cirrhotic patients are only detectable when Hb is Ͻ12 g/dL. This value is lower than that observed in anemic patients with iron deficiency and seems blunted and inadequate compared with the degree of anemia (15).…”
Section: Discussionmentioning
confidence: 95%
“…However, Siciliano et al 34 suggested an impaired EPO response in patients with liver cirrhosis. Moreover, Bruno et al 35 showed that an increase in Epo in patients with chronic liver diseases is lower than that observed in patients with iron-deficiency anemia and appears blunted and inadequate in comparison to the degree of anemia. The results of this study show that DPO application effectively reduces anemia in mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, as also unravelled by our large study, anaemia is certainly a major factor, and not only the current haemoglobin but also bleeding history or disorders predisposed to elevated EPO plasma levels. Siciliano and co-workers -as well as other groupsraise an interesting point in suggesting comparison of the EPO levels of liver disease patients with an Hb-matched anaemic control group, suggesting that EPO levels are not adequately upregulated with respect to the degree of anaemia [3,4]. This finding may have important clinical implications, because it could promote clinical trials for recombinant human EPO in advanced liver cirrhosis.…”
mentioning
confidence: 85%